Development of hypercontent–slow motion football teaching materials to improve learning motivation, critical thinking, and basic skills - Ridwan, Mochamad; Rohman, Mohammad Fathur; Tuasikal, Abdul Rachman; Kartiko, Dwi Cahyo; Yosika, Ghana Firsta (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to develop and test football teaching materials enriched with hypercontent and slow-motion media to increase students’ learning motivation, critical thinking, and basic football technical skills. The research conducted in this study falls under the development research type, utilizing the ADDIE model (Analysis-Design-Develop-Implement-Evaluate). In the evaluation phase of the ADDIE model, a quasi-experimental design was applied to determine the effectiveness of the developed materials. A total of 68 first-year students majoring in Sports Education participated in the study, divided equally into two groups: an experimental group (n = 34) that used the hypercontent–slow motion teaching materials, and a control group (n = 34) that followed conventional instruction. The soccer teaching materials based on hypercontent-slow motion were evaluated as highly suitable supporting media for lectures, receiving favorable scores from media experts (4.3), material experts (4.2), and learning design experts (4.17). The results showed significant improvements (p < 0.05) in learning motivation, critical thinking, and basic football technical abilities in the experimental group compared to the control group, indicating the effectiveness of the hypercontent–slow motion teaching materials. In conclusion, the soccer teaching materials based on slow motion enriched hypercontent have proven to be effective in enhancing various skills and aspects of learning, making them a valuable resource for students’ soccer education.